MEMBANGUN MOTIVASI KERJA RELAWAN DI PMI KOTA SEMARANG - Permana Putri, Vinda; Rahardjo, Mudji (Diponegoro Journal of Management, 2012)
This research reports on a study undertaken in an non profit organization PMI that engaged in humanity. The aims of this research is to examine and identify the intrinsic factors that influences volunteers motivation in PMI Semarang. The factors that used in this research are responsibility, recognition, the work itself and advancement. This research uses quantitative method. Data collected by questionnaires and sampling method used in this research is sensus . Sample used in this research are 98 respondents. Data test techniques used in this research are validity test, reliability test, classic assumption test, and multiple regression analysis using SPSS 16. The results of this research indicate that the intrinsic factors are responsibility, recognition, the work itself and advancement have a positive and significant influence with volunteers motivation in PMI Semarang. Variable the work itself has the biggest influence with coefficient values 0,322. Then variable recognition with coefficient values 0,258. Variable responsibility with coefficient values 0,237 and the last is variable advancement with coefficient values 0,212.